PERANCANGAN SISTEM INFOMASI PEMBELIAN DAN PENJUALAN BARANG BERBASIS WEB PADA TB BANGUN PERSADA - Luku Arizki Heraja Sanni (2023)
TB Persada Building Store is a business in the field of tools and materials where the data collection information system used is still manual. As in the case of goods data collection, incoming goods, sales, and reporting, everything is written in a small book and stored in a ledger. The aim of this research is to design an application that can simplify everything related to building material data collection. On the display side, this system uses the open source Conigniter 3 framework using the MVC model (model, view, and controller) which is very suitable for building dynamic websites more quickly and effectively. This system is expected to help performance in the management carried out by stores and is safer and more transparent compared to systems that still use paper. It is hoped that the information system for purchasing and selling goods will also be managed more effectively and efficiently.